2019
DOI: 10.3390/nu11061208
|View full text |Cite
|
Sign up to set email alerts
|

Use of vitamin and mineral supplements among adolescents living in Germany—Results from EsKiMo II

Abstract: Dietary supplements may contribute to nutrient intake; however, actual data on dietary supplement use among adolescents living in Germany are rare. The aim of this analysis was to describe the current use of dietary supplements, its determinants, and reasons of use. Changes in supplement use over time were evaluated by comparing the results with those from EsKiMo I (2006). Data from the Eating Study as a KiGGS Module EsKiMo II (2015–2017) were used to analyze supplement intake according to sociodemographic, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…This trend is consistent with our previous report [22]. However, the prevalence in adolescents was still lower than in the USA (32%) [13] or European countries (16.4-69.0%) [16,17,19]. New finding in this study is that the ratio of concomitant use of dietary supplement and medicine was also increased with children's age from 1.4% in one to three years to 6.0% in HS.…”
Section: Discussionsupporting
confidence: 92%
“…This trend is consistent with our previous report [22]. However, the prevalence in adolescents was still lower than in the USA (32%) [13] or European countries (16.4-69.0%) [16,17,19]. New finding in this study is that the ratio of concomitant use of dietary supplement and medicine was also increased with children's age from 1.4% in one to three years to 6.0% in HS.…”
Section: Discussionsupporting
confidence: 92%
“…A dietary supplement is defined by the Food and Drug Administration (FDA) as a product intended for ingestion that contains a “dietary ingredient” intended to add further nutritional value to (supplement) the diet. [1] Dietary supplements are used by millions in many forms such as multivitamins and it is commonly used as a result of self-diagnosed conditions and/or promote health[234] and the usage of supplements such as multivitamins has increased considerably in the past several years,[5] as it plays a key role in maintaining good health as a diet delivers essential nutrients while supplements complement said diet as it allows consumption of any deficiencies the diet lacks. [6] With increased health awareness, education and availability for dietary supplements would lead to overall wide usage.…”
Section: Introductionmentioning
confidence: 99%
“…Data included in this Special Issue are from large epidemiological studies including several multi-center [5,6] and multinational studies [3,7] as well as datasets from surveillance initiatives, such as the German Health Interview and Examination Survey for Children and Adolescents (KiGGS) [8,9], the U.S. National Health and Nutrition Examination Survey (NHANES) [10], and the WHO European Childhood Obesity Surveillance Initiative (WHO COSI) [11]. Three of the studies in this Special Issue reported on the co-occurrence of multiple health behaviors in the same children [6,8,11], in particular the clustering of low levels of physical activity levels and/or high screen times with a higher consumption of energy-dense foods [6,8].…”
mentioning
confidence: 99%
“…Two European studies evaluated the prevalence and determinants of dietary supplement use in children and adolescents, an important research question given that dietary supplement use has been implicated in preventable adverse drug events and emergency department visits in children and adolescents [21,22]. Data from the KiGGS Module EsKiMo II study showed that around 16% of adolescents in Germany use dietary supplements [9], and data from Eastern Poland reported that around 30% of children and adolescents use vitamin or mineral supplements [23]. Notably, the time frame for which supplement intake was queried was different in these two studies; in Germany the time frame was the previous four weeks and in Poland the past 12 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation